Princípios biomecânicos do aparelho extrabucal - Shimizu, Roberto Hideo [UNESP]; Ambrosio, Aldrieli R.; Shimizu, Isabela A.; Godoy-bezerra, Juliana De; Ribeiro, Jucienne Salgado; Staszak, Katiane Regina (Dental Press Editora, 2004)
The use of the headgear appliance for the treatment of Angle Class II malocclusion demands that the biomechanic principles are understood and applied so that the clinic case is conducted in a way that the side effects are minimized and the benefits maximized. Therefore, the orthodontist must be able to predict the effects of the inclination of the line of traction and its relation to the teeth and maxillary centers of resistance. Any rotation movement, inclination or translation of the teeth and maxillary and mandibular rotation clockwise or counter clockwise can be predict and planned when the orthodontist knows the mechanism that cause them, as well as the effects that the different types of traction produce in subjects with dolichofacial, mesofacial or brachyfacial types. Thus, the aim of this work is to present predominant and indispensable factors for the utilization of the headgear appliance for the treatment of Angle Class II malocclusion.

A utilização do aparelho extrabucal no tratamento da má oclusão de Classe II de Angle, exige que os princípios biomecânicos sejam entendidos e aplicados para que o caso clínico seja conduzido de maneira que os efeitos colaterais sejam minimizados e os benéficos maximizados. Para tanto, o ortodontista deve ser capaz de prever os efeitos da inclinação da linha de ação de força e sua relação com os centros de resistência da maxila e dos dentes. Quaisquer movimentos de rotação, inclinação ou translação dos dentes, bem como rotação horária ou anti-horária da maxila e da mandíbula, podem ser previstos e planejados quando o ortodontista conhece os mecanismos que os produzem, e também os efeitos que os diferentes tipos de tração produzem em indivíduos dolicofacial, mesofacial ou braquifacial. Assim, o intuito desse trabalho é apresentar fatores preponderantes e imprescindíveis para a utilização do aparelho extrabucal no tratamento da má oclusão de Classe II de Angle.
Biomechanic principles of the headgear appliance
Keywords: Angle Class II malocclusion; Extraoral traction appliances; Orthodontic treatment; Biomechanics; Má oclusão Classe II de Angle; Aparelhos de tração extrabucal; Tratamento ortodôntico; Biomecânica